2021
DOI: 10.1101/2021.08.05.455302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functionalized Biomimetic Hydrogels Enhance Salivary Stem/Progenitor Cell Organization

Abstract: Complex branched salivary structures remain challenging to replicate within implant ready hydrogels. We showed previously that hyaluronic acid (HA)-based hydrogels enable growth and organization of primary salivary-derived human stem/progenitor cells (hS/PCs) into multicellular spheroids. Here, we systematically functionalized three components of migration-permissive hydrogels to foster salivary tissue morphogenesis. We separately analyzed contributions of an enzymatically degradable crosslinker, a pendant int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The MMP degradation data in Figure 3c is an interesting contrast to one of our prior systems (Martinez et al 2021), which compared similar HA hydrogels, formed with either 100% PQ crosslinker, 100% PQ*, or 100% PEGDA. In that work by Martinez et al, gel pucks expanded in size when incubated with MMP-2, while the present work showed that susceptible gel pucks contracted.…”
Section: Discussionmentioning
confidence: 63%
“…The MMP degradation data in Figure 3c is an interesting contrast to one of our prior systems (Martinez et al 2021), which compared similar HA hydrogels, formed with either 100% PQ crosslinker, 100% PQ*, or 100% PEGDA. In that work by Martinez et al, gel pucks expanded in size when incubated with MMP-2, while the present work showed that susceptible gel pucks contracted.…”
Section: Discussionmentioning
confidence: 63%
“…Cells were resuspended in HA-SH solution, and then acrylate-PEG-GRGDS (73.7 mg/mL in PBS), acrylate-PEG-YIGSR (73.7 mg/mL), and acrylate-PEG-PQ-PEG-acrylate (37.0 mg/mL in PBS) were added at a volume ratio of 4:0.5:0.5:0.2:0.8 (HA-SH:acrylate-PEG-GRGDS:acrylate-PEG-YIGSR:acrylate-PEG-PQ-PEG-acrylate:PBS) for all experiments. The solution was mixed well, and then 42 µL of gel solution was dispensed into each well cavity of the PDMS mold, as described previously [ 17 ]. Filled molds were placed into the cell culture incubator at 37 °C for 45 min to allow gelation to occur; then, one drop of cell culture media was added to the top of each gel to prevent dehydration, and the molds were placed back into the incubator for 1–2 h. This allowed low-crosslinking-density hydrogels to crosslink more completely for ease of handling before the gels were scored around their circumference with the tip of a sterile needle.…”
Section: Methodsmentioning
confidence: 99%
“…ECM-derived hydrogels contain these motifs, such as RGD (Arginine-Glycine-Aspartic Acid), DGEA (Aspartic acid-Glycine-Glutamic acid-Alanine), YIGSR (Tyrosine-Isoleucine-Glycine-Serine-Arginine) [ 30 ], and heparan sulfate binding domains, which inherently support cell attachment, as opposed to natural bioinert materials such as alginate. So far, limited studies have evaluated the specific benefits of modifying and integrating binding ligands for SG three-dimensional culture [ 31 , 32 ].…”
Section: Tuning Ideal Hydrogel Properties For Sg Tissue Engineeringmentioning
confidence: 99%